2006
DOI: 10.1037/0022-3514.90.2.197
|View full text |Cite
|
Sign up to set email alerts
|

Temporal differences in trait self-ascription: When the self is seen as an other.

Abstract: Seven studies exploring people's tendency to make observer-like attributions about their past and future selves are presented. Studies 1 and 2 showed temporal differences in trait assessments that paralleled the classic actor-observer difference. Study 3 provided evidence against a motivational account of these differences. Studies 4-7 explored underlying mechanisms involving differences in the focus of attention of the sort linked to the classic actor-observer difference. In Study 4, people perceived past and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
293
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 254 publications
(310 citation statements)
references
References 46 publications
14
293
3
Order By: Relevance
“…It should be noted, however, that this should mostly be the case for judgment about a temporally proximal self (i.e., the self in the present or in the near past or future) than for judgment about a temporally distant self (i.e., the self in the distant past or future). Indeed, judgments about a temporally distant self should resemble judgments about others, that is, they should be based more on high-than low-level construal features (e.g., Nussbaum, Trope, & Liberman, 2003;Pronin & Ross, 2006;Wakslak, Nussbaum, Liberman, & Trope, in press). …”
Section: Projectionmentioning
confidence: 99%
“…It should be noted, however, that this should mostly be the case for judgment about a temporally proximal self (i.e., the self in the present or in the near past or future) than for judgment about a temporally distant self (i.e., the self in the distant past or future). Indeed, judgments about a temporally distant self should resemble judgments about others, that is, they should be based more on high-than low-level construal features (e.g., Nussbaum, Trope, & Liberman, 2003;Pronin & Ross, 2006;Wakslak, Nussbaum, Liberman, & Trope, in press). …”
Section: Projectionmentioning
confidence: 99%
“…Furthermore, attributions made about past selves more closely resemble attributions made about others than attributions regarding the present self (e.g. in terms of the tendency to make dispositional attributions; Pronin and Ross, 2006). Therefore, it seems that following personal changes, people process information regarding their past self as they would process information regarding others.…”
mentioning
confidence: 94%
“…There is evidence that when people perceive they have changed, they tend to distance themselves from their past self and regard it as 'another person' (Libby and Eibach, 2002;Pronin and Ross, 2006). For example, people frequently adopt a third-person visual perspective when recalling past behaviors that are discrepant with their present self-concept, as if they were looking at someone else (Libby and Eibach, 2002).…”
mentioning
confidence: 99%
“…Some philosophers have suggested that a person is a succession of overlapping but different selves, 79 and research in social psychology has revealed that when people feel they have changed, they tend to distance themselves from psychologically remote former selves, which are then regarded as "other persons". [80][81][82] Someone may, for example, have a mental model of who she was five years ago (e.g., knowing that she was shy) but may no longer identify herself with that model. Although she can recognize that the person to whom the mental model refers to was herself, she no longer identifies that model as "me" (i.e., her current self) because she feels she has changed (e.g., she feels she is not shy anymore).…”
Section: A Potential Role Of the Mpfc In Self-referential Processingmentioning
confidence: 99%